2013
DOI: 10.1136/bcr-2013-010417
|View full text |Cite
|
Sign up to set email alerts
|

The use of cannabinoids in chronic pain

Abstract: SUMMARYWe present the case of a 56-year-old man who developed chronic pain following the excision of a facial cancer that was poorly controlled despite multiple analgesic medications. Following the starting of nabilone (a synthetic cannabinoid) his pain control was greatly improved and this had a huge impact on his quality of life. We also managed to significantly reduce his doses of opioid analgesia and ketamine. We review the current literature regarding the medicinal use of cannabinoids, with an emphasis on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The International Pain Research Society has stated that pain is the fifth vital sign after blood pressure, pulse, respiration, and body temperature. As a long-term symptom, cancer pain has affected patients and their family members in terms of physiology, psychology, spirit, and quality of life (11). Studying the genes associated with PDAC cancer pain will therefore have significant clinical implications and will help to provide a foundation for PDAC patients' pain management.…”
Section: Protein Interaction Network Construction and Module Analysis...mentioning
confidence: 99%
“…The International Pain Research Society has stated that pain is the fifth vital sign after blood pressure, pulse, respiration, and body temperature. As a long-term symptom, cancer pain has affected patients and their family members in terms of physiology, psychology, spirit, and quality of life (11). Studying the genes associated with PDAC cancer pain will therefore have significant clinical implications and will help to provide a foundation for PDAC patients' pain management.…”
Section: Protein Interaction Network Construction and Module Analysis...mentioning
confidence: 99%
“…The new study has shown that chronic intake of marijuana can protect critical immune tissue from the damaging effects of HIV infection [30]. At present, AIDS and cancer patients utilize various drugs containing synthetic THC such as Dronabinolor Nabilone [31][32][33]. The drugs are used to decrease marijuana withdrawal symptoms as well as to increase appetite and prevent chemotherapy related nausea and vomiting [28,34,35].…”
Section: Therapeutic Uses Of Marijuanamentioning
confidence: 99%